(untitled) (Tempo e Argumento, 2010)
Migration processes to the United States are just as much about those migrants who leave Brazil as it is about those who remain, and also about those who return to Brazil (i.e.; returnees). Brazilian immigration to the United States is a relatively recent phenomenon that gained momentum in the 1980s in unprecedented numbers. How are these Portuguese-speaking Brazilian immigrants shaping and (re)creating new places and spaces, and what happens upon their eventual return to Brazil? How are migrant returnees experiencing changes in their livelihoods in two sending communities in Brazil, after living in two receiving communities in the United States? Using multiple methods and selected extracts from 273 in-depth and informal interviews, this paper addresses these questions by evaluating the changes incurred by migration. Brazilians (re)create transnational places and spaces through social, cultural, and economic practices, within receiving communities, but they also incorporate and add new elements to their livelihoods in sending communities of Piracanjuba, in the state of Goiás, and Governador Valadares, in the state of Minas Gerais, in Brazil. Brazilian migration processes have both positive and negative ramifications. However, the migration process is experienced differently by men and women. Men tend to experience an emasculation of sorts and are happier in Brazil, while women tend to indicate higher happiness levels in the United States.